Exploration of calcium and amino acids for children with primary cardiomyopathies based on genetic characteristics - Jiang, Shirui; Zhang, Ailin; Deng, Jiegang; Wang, Wei; Wang, Jingyu; Chen, Hongyu; Zhu, Liqin; Liu, Wei (Frontiers in Pediatrics, 2025)
BackgroundPediatric primary cardiomyopathies (PCMs) are rare diseases with complex causes and nonspecific treatment. The influence of electrolytes and amino acids (AAs) on cardiomyopathies has not been extensively studied. This study aimed to explore clinical characteristics and the usage of electrolytes and AAs in children with PCMs.MethodsChildren diagnosed with PCMs who had genetic test reports were included. Relevant information was collected and processed, and clinical characteristics and mutated genes were clarified. Gene databases were searched to explore related electrolytes and AAs in the treatment of PCMs. The effect of calcium was explored in children with DCM. Paired samples T tests and nonparametric Wilcoxon signed-rank tests were performed for comparison between before and after using calcium.ResultsIn this study, 27 children with gene test results were enrolled to perform gene-related analysis. The median age was 2.5 years old. Mutated genes were collected, including pathogenic, likely pathogenic, uncertain significance, and other mutations. The most frequently mutated genes related to dilated cardiomyopathy (DCM) were TTN, MYH7, NEXN, TNNI3, and SCN5A. In hypertrophic cardiomyopathy (HCM), MYBPC3, MYH7, PRKAG2, RAF1, and RBM20 were prevalent. Calcium and AAs (serine, cysteine, arginine, tyrosine, and alanine) were related to the mutated genes detected in children with PCMs. In addition, 17 children treated with calcium showed significant improvement in heart function.ConclusionsFor children with DCM, calcium supplements may be beneficial. AAs, including serine, cysteine, and arginine, could be used for supplementary treatment in children with DCM and HCM.